Hematologic profile of hemoglobin constant spring and its co-inheritance with hemoglobin C: a case report - Adzahar, Sumaiyah; Rahman, Sharifah Sakinah Syed Abdul; Nordin, Mohammad Hudzaifah; Rameli, Nabilah (Faculty of Medicine Universitas Indonesia, 2025)
Hemoglobin constant spring (Hb CS) is an alpha-globin variant characterized by an elongated alpha chain due to a mutation that leads to unstable hemoglobin (Hb) levels. Hemoglobin C (Hb C) is a beta-globin variant associated with mild hemolytic anemia. The co-inheritance of Hb CS and Hb C is uncommon and presents distinct hematologic features. We report the case of a 7-year-old Malaysian male who developed acute polyarthritis due to streptococcal infection. Routine blood tests revealed microcytic hypochromic anemia, suggestive of a thalassemia trait. Hb analysis via high-performance liquid chromatography and capillary electrophoresis detected low hemoglobin A levels with an additional peak in the Hb C zone. DNA analysis confirmed compound heterozygosity for Hb CS and Hb C. Family screening revealed that the mother is an Hb C carrier, and the father is an Hb CS carrier. This case report examined the hematological profile of a patient with this genetic combination.